Barriers and facilitators to cultural competence in rehabilitation services: a scoping review - Viviane Grandpierre; Victoria Milloy; Lindsey Sikora; Elizabeth Fitzpatrick; Roanne Thomas; Beth Potter (BMC Health Services Research, 2018)
Abstract Background There is an important need to evaluate whether rehabilitation services effectively address the needs of minority culture populations with North America’s increasingly diverse population. The objective of this paper was therefore to review and assess the state of knowledge of barriers and facilitators to cultural competence in rehabilitation services. Method Our scoping review focused on cultural competence in rehabilitation services. Rehabilitation services included in this review were: audiology, speech-language pathology, physiotherapy, and occupational therapy. A search strategy was developed to identify relevant articles published from inception of databases until April 2015. Titles and abstracts were screened by two independent reviewers according to specific eligibility criteria with the use of a liberal-accelerated approach. Full-text articles meeting inclusion criteria were then screened. Key study characteristics were abstracted by the first reviewer, and findings were verified by the second reviewer. Results After duplicates were removed, 4303 citations were screened. Included articles suggest that studies on cultural competence occur most frequently in occupational therapy (n = 17), followed by speech language pathology (n = 11), physiotherapy (n = 6), and finally audiology (n = 1). Primary barriers in rehabilitation services include language barriers, limited resources, and cultural barriers. Primary facilitators include cultural awareness amongst practitioners, cultural awareness in services, and explanations of health care systems. Conclusion To our knowledge, this review is the first to summarize barriers and facilitators to cultural competence in rehabilitation fields. Insufficient studies were found to draw any conclusions with regards to audiological services. Minimal perspectives based on patient/caregiver experiences in all rehabilitation fields underscore a research gap. Future studies should aim to explore both patient/caregiver and practitioner perspectives as such data can help inform culturally competent practices.